Analisis Pelaksanaan Kegiatan Sabtu Bersih di SD N 1 Demulih untuk Meningkatkan Kesadaran Lingkungan dan Kesehatan - Desak Putu Sri Sulatri (Universitas Palangka Raya, 2024)
This study aims to evaluate the implementation of the Clean Saturday program at SD N 1 Demulih in an effort to increase student awareness of environmental cleanliness and health. This program involves all elements of the school, including students and teachers, to create a clean and healthy environment. The research method used is descriptive qualitative, with data collected through observation, interviews, and documentation. The results of the study showed an increase in student awareness of environmental cleanliness and health after the implementation of Clean Saturday. Students became more disciplined in maintaining cleanliness, disposing of garbage in the appropriate place, and being more responsible for the condition of the school environment. However, there are challenges in terms of student participation and optimizing the use of cleaning facilities. This study concludes that the Clean Saturday program is effective in increasing students' environmental awareness, but ongoing support is needed to ensure that positive changes are maintained.